2008
DOI: 10.1152/jn.01388.2007
|View full text |Cite
|
Sign up to set email alerts
|

Dual Orexin Actions on Dorsal Raphe and Laterodorsal Tegmentum Neurons: Noisy Cation Current Activation and Selective Enhancement of Ca2+ Transients Mediated by L-Type Calcium Channels

Abstract: Kohlmeier KA, Watanabe S, Tyler CJ, Burlet S, Leonard CS. Dual orexin actions on dorsal raphe and laterodorsal tegmentum neurons: noisy cation current activation and selective enhancement of Ca 2ϩ transients mediated by L-type calcium channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
88
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 81 publications
13
88
0
Order By: Relevance
“…Previous reports have suggested that VGCCs provide an important pathway for orexin-A-induced calcium signal (Uramura et al, 2001;Xu et al, 2002;Kohlmeier et al, 2008). Therefore, the effect of orexin-A on VGCCs was investigated in cultured rat hypothalamic NPY neurons, which are involved in the orexigenic effect of orexin-A.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have suggested that VGCCs provide an important pathway for orexin-A-induced calcium signal (Uramura et al, 2001;Xu et al, 2002;Kohlmeier et al, 2008). Therefore, the effect of orexin-A on VGCCs was investigated in cultured rat hypothalamic NPY neurons, which are involved in the orexigenic effect of orexin-A.…”
Section: Resultsmentioning
confidence: 99%
“…AMPK can be indirectly activated by cytosolic free Ca 21 ([Ca 21 ] i ) via Ca 21 -sensitive calmodulin-dependent protein kinase kinases (CaMKKs) (Anderson et al, 2008;Bair et al, 2009;Fogarty et al, 2010). It has been demonstrated that appetite-regulating hormones such as ghrelin and orexin-A increase [Ca 21 ] i in many native neurons, including NPY neurons (Uramura et al, 2001;Xu et al, 2002;Kohlmeier et al, 2008). Thus, calcium-dependent activation of AMPK may couple orexin-A's action with the NPYergic system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenosine deaminase is a marker of histaminergic neurons (Senba et al, 1985). These antibodies have been used in previous studies and labeled neurons in a manner consistent with well known gene/protein expression patterns (Senba et al, 1985;Abumaria et al, 2007;Adamantidis et al, 2007;Kohlmeier et al, 2008). At 16 h later, the sections were processed according to the same protocol above, but instead of using DAB with nickel solution for the final staining step, we used DAB alone (Vector Laboratories) to create a brown staining product.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas OXA signals through both OX1R and OX2R, OXB is thought to operate mainly through OX2R (Scammell and Winrow, 2011;Gotter et al, 2012). The effects of OX peptides on their cognate receptors are mediated intracellularly through a rise in cytosolic calcium (Ca 21 cyt ) occurring primarily through intracellular calcium release channels, even if other mechanisms implicating voltage-dependent calcium channels (VDCCs) and transient receptor potential channels have also been described (Kukkonen et al, 2001;Kohlmeier et al, 2008;Nakamura et al, 2010).…”
Section: Introductionmentioning
confidence: 99%